Jean-Jacques Rousseau’s noble savage in contrast to the anarcho-primitivist return to nature - Gołda, Michał (Hybris, 2021)
The idea of "noble savage" presented by Jean Jacques Rousseau was used in the deliberations of anarcho-primitivists. The purpose of this paper is to compare Rousseau's "noble savage" with the contemporary "noble savage" of anarcho-primitivists. Rousseau's man living in a state of nature is a rhetorical figure by which the French philosopher wanted to consider the opposition of life in nature and outside of nature. To bring out the difference between people functioning in civilized societies and wild individuals remaining in full symbiosis with nature.According to him, by abandoning nature in favor of life in society, the noble savage lost many primal and natural qualities, gaining instead the profits needed for collective existence. Anarcho-primitivist technophobia expresses itself in the belief that science and technology are incapable of giving man happiness and lead to the degradation of the environment, the alienation of man from nature, and the enslavement of people by the system. The return to nature that they advocate is aimed at rejecting technology, civilization, and social supremacy, and shifting from a sedentary to a hunter-gatherer lifestyle. It is supposed to "reawaken" in people the happy, noble savage. But is it possible? Is the man living in symbiosis with nature, postulated by anarcho-primitivists, only a rhetorical figure, like the noble savage present in Rousseau's philosophy? Is a true return to nature possible, or is it just ideological speculation?